Clinical and Prognostic Value of Molecular Markers of Diffuse Large B-Cell Lymphoma - SM Rastorguev; DA Koroleva; ES Boulygina; SV Tsygankova; NG Goncharov; OS Naraikin; NG Gabeeva; EE Zvonkov; AV Nedoluzhko (Клиническая онкогематология)
Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoid tumor in adults which is associated with approximately 30–40 % of all non-Hodgkin’s lymphomas. Diagnostic criteria include diffuse growth of large anaplastic tumor cells, expression of В-cell markers, and a high proliferative index. Due to the development of molecular genetic technologies it became obvious that underlying cause of clinical diversity is a huge amount of genetic failures which determine epigenetic modification of gene expression, activation variability of certain signaling pathways, and immunological properties of tumor cells. The study and systemization of molecular markers present a significant trend in DLBCL diagnosis and treatment. This review discusses most important molecular markers and current view on their clinical value.